Improving the photoluminescence quantum yields of quantum dot films through a donor/acceptor system for near-IR LEDs. Issue 1 (11th October 2018) - Davis, Nathaniel. J. L. K.; Allardice, Jesse R.; Xiao, James; Karani, Arfa; Jellicoe, Tom C.; Rao, Akshay; Greenham, Neil C.
Abstract : The PLQE of QD films can be increased by the incorporation of a relatively small fraction of well-passivated acceptor QDs. Abstract : Near-infrared light-emitting diodes (LEDs) show potential for telecommunication and medical applications. Quantum dot nanocrystals (QDs), specifically lead chalcogenides, are candidate LED materials since they exhibit tuneable luminescence across the whole near-infrared region, but their surface structure must be carefully controlled to achieve efficient emission. We demonstrate an efficient donor–acceptor QD system by embedding low-energy QDs with high photoluminescence quantum efficiency (PLQE) into a matrix of higher-energy QDs with lower PLQE. We find that the overall PLQE of densely packed cross-linked QD films can be improved by the incorporation of a relatively small fraction of well-passivated acceptor QDs, also leading to improved LED performance. Excitations are transferred into the isolated low-energy acceptor QDs, where they recombine with high radiative efficiency.